The role of ideology in disagreements among economists: A quantitative analisis - Thomas Mayer (University of California, Department of Economics, 2000)
How justified is the charge that ideology strongly influences the allegedly objective opinions of economists? An analysis of a new survey of AEA members and of surveys by Fuchs et al of labor economists and public economists shows that value judgments and judgments about the government''s efficacy have some influence on the way economists think about what should be purely economic issues. But such influence is not strong enough to explain much of the disagreement among economists.
Keywords: 330; Ideologie; Ökonomen; USA; Meinung